Development of a Microwave-Driven In-Liquid Plasma Reactor for Nickel Mobilization from Saprolite: A Proof-of-Concept Study - Pria Gautama; Shinfuku Nomura; Vilia Darma Paramita; Nurfiansyah Nurfiansyah; A. Ariputra; Arfandy Arfandy; Muh. Firdan Nurdin (PT. Global Research Collaboration, 2026)
This proof-of-concept study evaluates nickel mobilization from saprolite using a water-only, 60 s treatment and a low-cost domestic-grade microwave platform. A domestic 2.45 GHz microwave oven was modified to generate in-liquid plasma at 450 W in 150 mL distilled water (aquadest). Saprolite (<30 mesh, 10 g) was treated for 60 s, reaching a measured liquid temperature of 56 °C. The aqueous extract was analysed by atomic absorption spectroscopy (AAS), and the recovered solid was characterized by X-ray fluorescence (XRF). AAS detected 20.789 mg/L Ni in the plasma-treated extract. XRF showed that the normalized NiO mass fraction decreased from 1.6569 mass% in untreated saprolite to 1.4397 mass% after treatment, equivalent to a 13.1% relative compositional decrease; this value is not an extraction-efficiency figure. Fe₂O₃ remained nearly unchanged. The liquid- and solid-phase observations are consistent in direction and support nickel mobilization under the tested conditions. However, their implied magnitudes differ, and the absence of dry residue mass and complete liquid-recovery data prevents mass-balance closure and calculation of extraction efficiency.